Search 75,671 tutors
FIND TUTORS
Ask a question
0 0

-4(2-3x)=7-2(x-3)

Tutors, please sign in to answer this question.

2 Answers

-4(2-3x)=7-2(x-3)     *first use the distributive property Ex. a(b+c)=ab+ac

-8+12x=7-2x+6         *get all the terms with "x's" on each side.

12x+2x=7+6+8          *Collect like terms. Ex. 3x+5x=8x  (3+5=8)*they both have "x" so add coefficients.

14x=21                     *divide by 14 on both side to get "x" by itself.

x=21/14                    *simpify

x=3/2                       *Answer

Check by plugging 3/2 for "x" and evaluate. You should get 10=10, thus confirming the answer for "x" to be true.

(-4) * (2 - 3x) = 7 + (-2) * (x - 3)
(-4) * 2 - (-4) * 3x = 7 + (-2) * x - (-2) * 3 (distributive property)
 -8 + 12x = 7 - 2x + 6
+8             +8  
        12x = (7 + 8 + 6) - 2x
      + 2x                     + 2x 
        14x = 21 -----> 14x/14 = 21/14 -----> x = 3/2 = 1.5

Comments

Comment